Pengembangan Kapasitas (Capacity Building) Sumber Daya Manusia Desa Wisata Di Desa Pao Kecamatan Tombolo Pao Kabupaten Gowa - Fajar, Nur; Haning, Moh Thahir; Yunus, Muhammad (Department of Public Administration, Muhammadiyah University of Makassar, 2023)
This study aims to determine the development of Tourism Villages located in Pao Village, Tombolo Pao District, Gowa Regency. The method used in this study is a qualitative method, with data collection techniques through observation and interviews. The data analysis is carried out, starting from reduction, presentation of data, verification and drawing conclusions. The results showed that human resource capacity development in the development of tourism villages in Pao Village had not gone well. Recruitment has not been good because there are no clear procedures, the training system for Tourism Village object managers is not sustainable, and the a lack of training support infrastructure. The payroll system for Tourism Village object managers does not have a special budget, and working conditions are not good due to the lack of availability of supporting facilities and infrastructure for workers or tourism object managers so work quality and work motivation are low.